The development of I-store application for PPSUG, Uitm Perlis / Nur Afiqah Alias - Alias, Nur Afiqah (2022)
Today, mobile application (App) is a new emerging mobile technology and has been widely used. This new mobile artefact not only overturns the traditional business model of mobile industry, but also creates new avenues of mobile market opportunities. But Mobile Application uses and development is a new and rapidly growing sector. The aim of this study is to develop a mobile app that can be access by PPSUG UiTM Perlis student and staff for the purposes of equipment management. As to achieve the aim of the research, the following objectives have been identified which is to design an app for student in order to improve user accessibility and time availability of the surveying equipment and to encourage the student to practise paperless system. In this study, the methodology used is divided into four phase which is the planning and observation, data collection, designing and coding and lastly results and analysis. By this study, this mobile app can help the student and staff during the process of borrowing and returning the surveying equipment. Therefore, it can increase the awareness regarding the important of paperless system among the student of PPSUG UiTM Perlis.